Modeling of sound radiation by a beam - Zaporozhets, А.І.; Tokarev, V.І.; Hufenbaсh, Werner; Marburg, Shtefen; Taeger, Olaf; Modler, Nils; Dannemann, Martin (Proceedings of National Aviation University (archive), 2005)
An analytical formulation and numerical analysis are presented for the vibration and following noise radiation of a simply supported beam. The analytical solution was found in a form that is appropriate to describe the control of the beam vibration using active structures. The modeling approach can be used for forming of feedback control of the system of vibration loads by means of distribution of the actuators along the beam length.